High Selectivity Cascaded Quadruplet Bandpass Filter with Three Pairs of Transmission Zeros. Issue 5 (1st September 2017) - Chen, Jianfeng; Chen, Fuchang; Li, Runshuo; Xie, Zeming; Chu, Qingxin
Abstract : A novel microstrip Cascaded quadruplet (CQ) bandpass filter using quarter wavelength resonators and three‐quarter wavelength resonators is proposed. Based on cross coupling and source‐load coupling, three pairs of finite transmission zeros are generated at the stopband. As a result, the out‐of‐band rejection can be enhanced and high selectivity is achieved. Based on the proposed structure, a cascaded quadruplet filter centering at 3.0GHz is designed and fabricated. Good agreement between the measured and simulated data is obtained.